Corticosteroids as adjunctive therapy with antibiotics in the treatment of children with septic arthritis: a meta-analysis - Qin YF; Li ZJ; Li H (Dove Medical Press, 2018)
Ya-fei Qin, Zhi-jun Li, Hui Li Department of Orthopedics, Tianjin Medical University General Hospital, Tianjin 300052, China Purpose: We performed a meta-analysis to systematically assess the effect of adjunctive administration of dexamethasone with antibiotic therapy in the clinical course of septic arthritis (SA) in children. Method: Potential academic articles were identified from the Cochrane Library, Medline, PubMed, Embase, ScienceDirect, and other databases. The time range we retrieved from was from the inception of electronic databases to January 2018. The reference lists of identified studies were manually checked to identify other potentially eligible trials. The STATA version 11.0 (Stata Corporation, College Station, TX, USA) was used to analyze the pooled data. Results: Three randomized controlled trials, and one retrospective cohort study were included in the meta-analysis. There were significant differences in the days of hospitalization (mean difference [MD] = -4.226, 95% CI: -4.785 to -3.667, P=0.001), the days of intravenous antibiotics treatment (MD = -3.593, 95% CI: -4.825 to -2.361, P=0.001), the days of oral antibiotics treatment (MD = -1.658, 95% CI: -2.539 to -0.777, P=0.001), and the days to normalization of C-reactive protein (MD = -3.075, 95% CI: -3.362 to -2.788, P=0.001). Conclusion: The present meta-analysis base points strongly toward a beneficial effect for corticosteroids in SA. Corticosteroids as adjunctive therapy with antibiotics in the treatment of children with SA could shorten the number of days of hospitalization, the days of intravenous antibiotics treatment, the days of oral antibiotics treatment, and the days to normalization of C-reactive protein. We recommend corticosteroids as adjunctive therapy with antibiotics in the treatment of children with SA. Keywords: glucocorticoids, child, septic arthritis, meta-analysis